Case report: Matricide by a 17-year old boy with Asperger's syndrome. (November 2016) - Lazaratou, Helen; Giannopoulou, Ioanna; Anomitri, Chrysanthi; Douzenis, Athanasios
Abstract: This case study presents a 17-year-old boy with Asperger's syndrome (AS) who was charged with matricide. The adolescent had neither prior history of aggression and violent behavior nor an established history of co-morbid disorder. The case illustrates challenging clinical issues of forensic relevance within the framework of psychiatric evaluation of young people with AS committing violent crimes. It exemplifies how the failure to recognize AS-related vulnerabilities and special needs when compounded by cumulative stress can lead to a grave outcome. Highlights: A case report of a 17-year-old boy diagnosed with Asperger's syndrome (AS) who was charged with matricide Illustrates clinical issues of forensic relevance within the framework of psychiatric evaluation of adolescents with AS Exemplifies how missed opportunities in recognizing and addressing individualized therapeutic needs may lead to violent crime